Blood pressure control in conventional hemodialysis. Issue 6 (6th August 2018) - Georgianos, Panagiotis I.; Agarwal, Rajiv
Abstract: Hypertension among patients on hemodialysis is common, difficult to diagnose and often inadequately controlled. Although specific blood pressure (BP) targets in this particular population are not yet established, meta‐analyses of randomized trials showed that deliberate BP‐lowering with antihypertensive drugs improves clinical outcomes in hemodialysis patients. BP‐lowering in these individuals should initially utilize nonpharmacological strategies aiming to control sodium and volume overload. Accordingly, restricting dietary sodium intake, eliminating intradialytic sodium gain via individualized dialysate sodium prescription, optimally assessing and managing dry‐weight and providing a sufficient duration of dialysis are first‐line treatment considerations to control BP. If BP remains uncontrolled despite the adequate management of volume, antihypertensive therapy is the next consideration. Contrary to nonhemodialysis populations, emerging clinical‐trial evidence suggests that among those on hemodialysis, β‐blockers are more effective than agents blocking the renin‐angiotensin‐system (RAS) in reducing BP levels and protecting from serious adverse cardiovascular complications. Accordingly, β‐blockade is our first‐line approach in pharmacotherapy of hypertension. Long‐acting calcium‐channel‐blockers and RAS‐blockers are our next considerations, taking into account the comorbidities and the overall risk profile of each individual patient. Additional research efforts, mainly randomized trials, are clearly warranted in order to elucidate aspects of management that remain elusive in hypertensive dialysis patients.